DIFFERENT APPROACHES TO TEACHING SOCIAL SKILLS TO PRESCHOOLERS - Rafiah Kassim; Fatin Aliana Mohd Radzi; Sharifah Muzlia Syed Mustafa (Journal of Islamic, Social, Economics and Development, 2024)
The aim of this paper is to examine various theories related to learning in young children, with a particular focus on social skills. It is widely recognized that instilling social skills at an early age can foster children's interest in learning and contribute to their overall educational experience. Aspiring preschool teachers who are pursuing a degree in early childhood education are provided with instruction on learning approaches and theories that are relevant to young children's social development. In order to explore these theories, this study specifically examines the approaches of John Dewey, Vygotsky, Skinner, and Reggio Emilia. Despite the advancements in 21st-century education, the inclusion of social skills in preschool curricula needs to be critically reassessed. This reassessment will enhance teachers' understanding of the importance of preparing children to navigate the ever-changing landscape of academic knowledge, which is closely intertwined with social skills. By doing so, children will be better equipped to adapt to and manage changes throughout their lives. This presentation is based on a doctoral study that investigates the effectiveness of teaching approaches in preschools for instilling social skills. The cultivation of social skills is a crucial factor for both academic and social success, as the absence of these skills can lead to negative behaviors. Therefore, prior to delving into the significance of social skills for academic and lifelong achievement, it is essential to acknowledge the inclusion of social skills in the curriculum, as supported by previous research. This inclusion paves the way for the development of competent preschool teachers and enables children to effectively interact with the world.